Correction to: Early outcomes of tapering jejunoplasty by antimesenteric seromuscular stripping and mucosal inversion for proximal jejunal atresia - Mahmoud Marei Marei; Mohamed Hamed Abouelfadl; Ahmed Arafa Elsayed Rawwash; Hamed Mahmoud Seleim; Wesam Mohamed Mahmoud; Tamer Yassin Mohamed Yassin; Gamal Hassan El-Tagy (SpringerOpen, 2020)
An amendment to this paper has been published and can be accessed via the original article.